Perceptual metaphor as a mean of creating an image of a person in Russian dialect language - Педченко, Людмила Вадимовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article explores the metaphorical potential of perceptual lexicon in Russian dialect language in the aspect of the formation of the "image of a person", the patterns of interaction of the perception system and other "bodily" and "spiritual" human systems in the Russian language picture of the world are revealed. The author calls into question the idea of Y. Apresyan about the binary organization of the systems that form the image of a person in the Russian language picture of the world, on the pairing of systems of perception and intellect. The analysis of dialect lexemes serving various modes of perception shows that the metaphorical potential of perceptual vocabulary is not limited to the intellectual sphere. Different modes of perception show a closer interaction with certain systems: vision - with intellect and emotions, hearing - with intellect and speech, smelling - with actions and intellect, taste, pain and temperature sensations - with emotions, tactile sensations are associated with almost all systems. The variety of models of perceptual metaphor proves that perception, which is the foundation on which cognition and assessment of a person around the world is based, is associated with all systems that form the "image of man" – intellect, actions and activities, physiological reactions, emotions, speech etc.